2-Amino-4-(2,4-dihydroxyphenyl) quinoline-3-carbonitrile as sustainable corrosion inhibitor for SAE 1006 steel in 1 M HCl: Electrochemical and surface investigation - Verma C.; Quraishi M.A. (My University, 2025)
The corrosion inhibition efficiency of 2-amino-4-(2,4-dihydroxyphenyl) quinoline-3-carbonitrile (ADQC) on SAE 1006 steel has been investigated using electrochemical (EIS and Polarization), surface (SEM, EDX and AFM) and quantum chemical calculation methods. Results showed that inhibition efficiency increases with increasing ADQC concentration and maximum value of 96.12% was obtained at 25 mg/L concentration. EIS results showed the ADQC inhibits SAE 1006 steel corrosion becoming the adsorbate at metal/electrolyte interfaces. Polarization study showed that ADQC acts as cathodic type inhibitor. SEM, EDX and AFM finding supported the adsorption of ADQC on the mild steel surface. The quantum chemical calculations provide good insight about the adsorption and inhibition mechanism of ADQC. The experimental and quantum chemical calculation results were in good agreement. © 2016 University of Bahrain